Projected impacts of warming seas on commercially fished species at a biogeographic boundary of the European continental shelf. Issue 11 (9th August 2020) - Maltby, Katherine M.; Rutterford, Louise A.; Tinker, Jonathan; Genner, Martin J.; Simpson, Stephen D.
Abstract: Projecting the future effects of climate change on marine fished populations can help prepare the fishing industry and management systems for resulting ecological, social and economic changes. Generating projections using multiple climate scenarios can provide valuable insights for fisheries stakeholders regarding uncertainty arising from future climate data. Using a range of climate projections based on the Intergovernmental Panel on Climate Change A1B, RCP4.5 and RCP8.5 climate scenarios, we modelled abundance of eight commercially important bottom dwelling fish species across the Celtic Sea, English Channel and southern North Sea through the 21st century. This region spans a faunal boundary between cooler northern waters and warmer southern waters, where mean sea surface temperatures are projected to rise by 2 to 4°C by 2098. For each species, Generalized Additive Models were trained on spatially explicit abundance data from six surveys between 2001 and 2010. Annual and seasonal temperatures were key drivers of species abundance patterns. Models were used to project species abundance for each decade through to 2090. Projections suggest important future changes in the availability and catchability of fish species, with projected increases in abundance of red mullet Mullus surmuletus L., Dover sole Solea solea L., John dory Zeus faber L. and lemon sole Microstomus kitt L. and decreases in abundance of Atlantic cod Gadus morhua L., anglerfish Lophius piscatorius L. and megrim Lepidorhombus whiffiagonis L. European plaice Pleuronectes platessa L. appeared less affected by projected temperature changes. Most projected abundance responses were comparable among climate projections, but uncertainty in the rate and magnitude of changes often increased substantially beyond 2040. Synthesis and applications . These results indicate potential risks as well as some opportunities for demersal fisheries under climate change. These changes will challenge current management systems, with implications for decisions on target fishing mortality rates, fishing effort and allowable catches. Increasingly flexible and adaptive approaches that reduce climate impacts on species while also supporting industry adaptation are required. Abstract : These results indicate potential risks as well as some opportunities for demersal fisheries under climate change. These changes will challenge current management systems, with implications for decisions on target fishing mortality rates, fishing effort and allowable catches. Increasingly flexible and adaptive approaches that reduce climate impacts on species while also supporting industry adaptation are required.